THE PROBLEMS OF SOCIAL AND PROFESSIONAL ADAPTATION OF THE STUDENTS WITH INTELLECTUAL ACTIVITY ISORDER - Elena A. Chereneva; Inessa G. Zaglyda; Julya A. Ptakhina; Natalya G. Klimkovitch; Tatyana A. Kochukova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article describes and analyzes the problems of social and professional adaptation of the students with mental disorder presented on the base of the psychological and pedagogical support school of general education № 104, the city of Kemerovo. Children with intellectual activity disorder of various level study at the school. The main results of the practical analyzes of the problem, the factors influencing the results of profession oriented and profession adjustment work and the contradictions are revealed. It’s pointed out that the purposeful work on the profession orientation of the children with intellectual activity disorder is one of the priority course of the labour education. But we have supposed that the results are to be minute without close cooperation between various organizations and departments for the social and professional adaptation of the students with intellectual activity disorder.